Constitutive activation of DIA1 (DIAPH1) via C‐terminal truncation causes human sensorineural hearing loss - Takehiko Ueyama; Yuzuru Ninoyu; Shin‐ya Nishio; Takushi Miyoshi; Hiroko Torii; Koji Nishimura; Kazuma Sugahara; Hideaki Sakata; Dean Thumkeo; Hirofumi Sakaguchi; Naoki Watanabe; Shin‐ichi Usami; et al. (EMBO Molecular Medicine, 2016)
Abstract DIAPH1 encodes human DIA1, a formin protein that elongates unbranched actin. The c.3634+1G>T DIAPH1 mutation causes autosomal dominant nonsyndromic sensorineural hearing loss, DFNA1, characterized by progressive deafness starting in childhood. The mutation occurs near the C‐terminus of the diaphanous autoregulatory domain (DAD) of DIA1, which interacts with its N‐terminal diaphanous inhibitory domain (DID), and may engender constitutive activation of DIA1. However, the underlying pathogenesis that causes DFNA1 is unclear. We describe a novel patient‐derived DIAPH1 mutation (c.3610C>T) in two unrelated families, which results in early termination prior to a basic amino acid motif (RRKR1204–1207) at the DAD C‐terminus. The mutant DIA1(R1204X) disrupted the autoinhibitory DID‐DAD interaction and was constitutively active. This unscheduled activity caused increased rates of directional actin polymerization movement and induced formation of elongated microvilli. Mice expressing FLAG‐tagged DIA1(R1204X) experienced progressive deafness and hair cell loss at the basal turn and had various morphological abnormalities in stereocilia (short, fused, elongated, sparse). Thus, the basic region of the DAD mediates DIA1 autoinhibition; disruption of the DID‐DAD interaction and consequent activation of DIA1(R1204X) causes DFNA1.